Attitudes and experiences of health care professionals when caring for transgender men undergoing fertility preservation by egg freezing: a qualitative study - Gabriela Armuand; Cecilia Dhejne; Jan I. Olofsson; Margareta Stefenson; Kenny A. Rodriguez-Wallberg (SAGE Publishing, 2020)
Background: As gender-affirming treatment may have a negative impact on fertility, reproductive health counseling to patients seeking medical or surgical gender-affirming treatment should be provided, including the option to undergo fertility preservation (FP). Experiences of transgender men undergoing FP treatments aimed at oocyte freezing have reported a negative impact of the treatments on gender dysphoria. No previous studies have investigated the experiences of health care professionals' (HCP) when caring for transgender men undergoing such treatments. Aim: The aim of this study was to investigate HCP's attitudes and experiences when meeting transgender men undergoing FP through oocyte freezing. Methods: Individual interviews were conducted in 2016 with 13 HCPs working at a Reproductive Medicine clinic in Sweden. Data were analyzed by thematic content analysis. Results: The main theme found, How to maintain professionalism , showed that HCPs experienced important challenges to their professionalism when their preconceived opinions and values about gender and transgender were confronted. Discussion: Our findings demonstrate the need of continuous efforts on assessing learning needs as well as addressing preconceived opinions and values of HCP. By gaining knowledge and self-confidence in the care of transgender individuals undergoing FP, a professional care for transgender people can be achieved and a safe environment can be established for the patients. This in turn may alleviate some of the distress that may arise when transgender men undergo FP.